Promising directions of laboratory diagnostics in spores and fitness - H. M. Zaharodny; N. V. Sherash; A. N. Budko; N. V. Shvedova (National Electronic Information Consortium (NEICON), 2021)
The article describes the main biomarkers for determining human adaptation to physical activity. Analyzed modern scientific publications on the criteria of individual tolerance of food products, studied promising directions of personalized correction of the diet. The authors have formed a group of valid (sports-specific) laboratory indicators, it is proposed to pay close attention to the reference values of laboratory equipment that have "their own" norms. A promising direction of laboratory diagnostic work is the formation of reliable and accessible complementary criteria that are at the "junction" of functional and instrumental diagnostic methods. Metabolomics is viewed as a young but highly effective science for detecting highly specific metabolic characteristics of human health. The authors proposed the main directions of scientific research in laboratory diagnostics in sports.